Falls After Dysvascular Transtibial Amputation: A Secondary Analysis of Falling Characteristics and Reduced Physical Performance. Issue 1 (6th May 2020) - Anderson, Chelsey B.; Miller, Matthew J.; Murray, Amanda M.; Fields, Thomas T.; So, Noel F.; Christiansen, Cory L.
Abstract : Introduction: Over half of all people with lower limb amputation (LLA) experience at least one fall annually. Furthermore, the majority of LLAs result from dysvascular health complications, contributing to balance deficits. However, fall‐related research specific to dysvascular LLA remains limited. Objective: To characterize falls among adults with dysvascular LLA, using an existing Fall‐Type Classification Framework and to describe the functional characteristics of participants across the framework categories. Design: Secondary data analysis from two randomized controlled trials. Setting: Outpatient setting. Participants: People (n = 69) 6 months to 5 years from dysvascular lower extremity amputation, who were ≥50 years of age and independently ambulatory using a prosthesis. Intervention: None. Outcome: Descriptions of self‐reported falls were collected on a weekly basis for 12 weeks, and analyzed using an existing Fall‐Type Classification Framework. Fall frequencies, estimated count, and estimated proportions were compared across all framework categories, with 95% confidence intervals. Functional measures (Timed Up and Go, Two Minute Walk, Five Meter Walk, and average step count) were collected, and averages for each participant who experienced a fall were calculated. Results: Thirty participants (43.5%) reported 42 falls within 12 weeks. A variety of fall types were described. Incidence of falls was highest for intrinsic destabilization sources, from incorrect weight shift patterns during transfer activities. Conclusion: Patients with dysvascular LLAs experience a variety of fall types. The high frequency of intrinsically sourced, incorrect weight‐shift falls during transfer activities emphasizes the need to focus rehabilitation efforts on improving postural control in patients with dysvascular LLAs during activities such as reaching, turning, and transferring.